Evaluating population histories in Patagonia and Tierra del Fuego, Chile, using ancient mitochondrial and Y‐chromosomal DNA. Issue 1 (2nd November 2022) - Balentine, Christina M.; Alfonso‐Durruty, Marta; Reynolds, Austin W.; Vilar, Miguel; Morello, Flavia; Román, Manuel San; Springs, Lauren C.; Smith, Rick W. A.; Archer, Samantha M.; Mata‐Míguez, Jaime; Wing, Natalie; Bolnick, Deborah A.
Abstract: Objectives: This study aims to characterize the genetic histories of ancient hunter‐gatherer groups in Fuego‐Patagonia (Chile) with distinct Marine, Terrestrial, and Mixed Economy subsistence strategies. Mitochondrial (mtDNA) and Y‐chromosome data were generated to test three hypotheses. H0 : All individuals were drawn from the same panmictic population; H1 : Terrestrial groups first populated the region and gave rise to highly specialized Marine groups by 7, 500 cal BP; or H2 : Marine and Terrestrial groups represent distinct ancestral lineages who migrated independently into the region. Methods: Ancient DNA was extracted from the teeth of 50 Fuegian‐Patagonian individuals dating from 6, 895 cal BP to after European arrival, and analyzed alongside other individuals from previous studies. Individuals were assigned to Marine, Terrestrial, and Mixed Economy groups based on archeological context and stable isotope diet inferences, and mtDNA (HVR1/2) and Y‐chromosome variation was analyzed. Results: Endogenous aDNA was obtained from 49/50 (98%) individuals. Haplotype diversities, FST comparisons, and exact tests of population differentiation showed that Marine groups were significantly different from Terrestrial groups based on mtDNA ( p < 0.05). No statistically significant differences were found between Terrestrial and Mixed Economy groups. Demographic simulations support models in which Marine groups diverged from the others by 14, 000 cal BP. Y‐chromosome results showed similar patterns but were not statistically significant due to small sample sizes and allelic dropout. Discussion: These results support the hypothesis that Marine and Terrestrial economic groups represent distinct ancestral lineages who diverged during the time populations were expanding in the Americas, and may represent independent migrations into Fuego‐Patagonia. Abstract : Mitochondrial DNA lineages (haplogroups) show that many Marine individuals (left) belong to different haplogroups compared to Terrestrial (middle) and Mixed Economy individuals (right). This suggests a distinct ancestry of the Marine group. Color represents haplogroup and size of pie chart represents number of grouped archaeological sites (with one or more individuals per site).